Scintigraphy and exogenous creatinine clearance to assess renal function in a Newfoundland dog with ureteral ectopia. Issue 1 (29th November 2013) - Queau, Yann; Larsen, Jennifer A.; Johnson, Eric G.; Westropp, Jodi L.
Abstract : A nine‐month‐old intact female Newfoundland dog was presented for evaluation of an ectopic ureter without lower urinary tract signs. Due to progression of the disease and periodic urinary infections, a nephrectomy and uretectomy were performed after assessment of global and individual renal function with complementary tools. Ectopic insertion of the left ureter with hydronephrosis was revealed by ultrasound, cystoscopy and contrast uretrogram. Individual glomerular filtration rate of the contralateral kidney estimated by plasma exogenous creatinine clearance and renal scintigraphy was deemed sufficient to remove the left kidney safely. A left nephrectomy and uterectomy were performed without complications, and periodic monitoring of the glomerular filtration rate revealed stable renal function during the follow‐up period of two years. The dog remained continent and free of urinary infections. In this case of ureteral ectopia in a dog, complementary diagnostic tools were used to assess renal function and plan interventional treatment.